2016
DOI: 10.1186/s12863-016-0353-x
|View full text |Cite
|
Sign up to set email alerts
|

Study on LOC426217 as a candidate gene for beak deformity in chicken

Abstract: BackgroundThe beak deformity (crossed beaks) was found in some indigenous chickens of China, such as Beijing-You (BJY), Qingyuan Partridge, and Huxu Chickens. Birds with deformed beaks have reduced feed intake and drinking, impeded growth rate, and poor production performance. Beak deformity reduces the economy of poultry industry and affects animal welfare as well. The genetic basis of this malformation remains incompletely understood. LOC426217, also named claw keratin-like, was the most up-regulated gene in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…It was estimated that 0.32% of all wild birds have crossed beaks [ 11 ]. In a recent study, prevalence ranging from 1 to 3% was documented for local Chinese chicken breeds [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was estimated that 0.32% of all wild birds have crossed beaks [ 11 ]. In a recent study, prevalence ranging from 1 to 3% was documented for local Chinese chicken breeds [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the identified genes belonged to the keratin family, as well as genes coding for proteins important in the biosynthesis of unsaturated fatty acids and the metabolism of glycerolipids. A follow-up study on the most promising gene LOC426217 found five variants that differed significantly between chickens with crossed beaks and normal controls [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cross-beaks are a disease resulting in economic loss for the poultry industry and comprise 1% to 3% in Chinese local chickens [2]. A beak consists of multiple facial prominences.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-beak is a dysmorphology relating to deformed beaks and has been suggested as a threat to animal welfare breeding. There are 1%-3% of Chinese native chickens that have beak deformities, leading to great economic loss and animal welfare issues in the poultry industry [1][2][3]. Typically, cross-beaks refer to the misalignment of upper and lower beaks.…”
Section: Introductionmentioning
confidence: 99%
“…unsaturated fatty acid biosynthesis and glycerolipid metabolism) that are associated with crossed beaks in chickens (Bai et al . , ).…”
Section: Introductionmentioning
confidence: 99%